Laminin enhances β(2)-adrenergic receptor stimulation of L-type Ca(2+) current via cytosolic phospholipase A(2) signalling in cat atrial myocytes - Pabbidi, M R (Blackwell Science Inc, 2009)
We previously reported that attachment of atrial myocytes to the extracellular matrix protein laminin (LMN), decreases adenylate cyclase (AC)/cAMP and increases β(2)-adrenergic receptor (AR) stimulation of L-type Ca(2+) current (I(Ca,L)). This study therefore sought to determine whether LMN enhances β(2)-AR signalling via a cAMP-independent mechanism, i.e. cytosolic phospholipase A(2) (cPLA(2)) signalling. Studies were performed on acutely isolated atrial myocytes plated on uncoated coverslips (−LMN) or coverslips coated with LMN (+LMN). As previously reported, 0.1 μm zinterol (zint-β(2)-AR) stimulation of I(Ca,L) was larger in +LMN than −LMN myocytes. In +LMN myocytes, zint-β(2)-AR stimulation of I(Ca,L) was inhibited by inhibition of cPLA(2) by arachidonyltrifluoromethyl ketone (AACOCF(3); 10 μm), inhibition of G(i) by pertussis toxin and chelation of intracellular Ca(2+) by 10 μm BAPTA-AM. In contrast to zinterol, stimulation of I(Ca,L) by fenoterol (fen-β(2)-AR), a β(2)-AR agonist that acts exclusively via G(s) signalling, was smaller in +LMN than −LMN myocytes. Arachidonic acid (AA; 5 μm) stimulated I(Ca,L) to a similar extent in −LMN and +LMN myocytes. Inhibition of cAMP-dependent protein kinase A (cAMP/PKA) by either 5 μm H−89 or 1 μm KT5720 in −LMN myocytes mimicked the effects of +LMN myocytes to enhance zint-β(2)-AR stimulation of I(Ca,L), which was blocked by 10 μm AACOCF(3). In contrast, H−89 inhibited fen-β(2)-AR stimulation of I(Ca,L), which was unchanged by AACOCF(3). Inhibition of ERK1/2 by 1 μm U0126 inhibited zint-β(2)-AR stimulation of I(Ca,L) in +LMN myocytes and −LMN myocytes in which cAMP/PKA was inhibited by KT5720. In −LMN myocytes, cytochalasin D prevented inhibition of cAMP/PKA from enhancing zint-β(2)-AR stimulation of I(Ca,L). We conclude that LMN enhances zint-β(2)-AR stimulation of I(Ca,L) via G(i)/ERK1/2/cPLA(2)/AA signalling which is activated by concomitant inhibition of cAMP/PKA signalling and dependent on the actin cytoskeleton. These findings provide new insight into the cellular mechanisms by which the extracellular matrix can remodel β(2)-AR signalling in atrial muscle.